Reconfigurable microfluidic platform in ice - Varejka, M. (Cranfield University, 2008)
Microfluidic devices are popular tools in the biotechnology industry where they provide smaller reagent requirements, high speed of analysis and the possibility for automation. The aim of the project is to make a flexible biocompatible microfluidic platform adapted to different specific applications, mainly analytical and separations which parameters and configuration can be changed multiple times by changing corresponding computer programme. The current project has been supported by Vice Chancellor Trans-Campus Iinitiative. Channels and various design geometries can easily and rapidly be marked on ice with a CO2 laser. Within seconds a microchannel pattern of features as small as 100 µm were obtained. The channels and design cavity dimensions are governed by the ratio of laser power by the beam velocity. The channels created in ice stay open for a duration which depend on their geometry and therefore on the ratio of the laser beam power by the beam velocity. Microchannels were created with a power/velocity ratio between 0.4 and 20 W/m. In this range of settings, the channels were 300 µm wide and stayed open for 2 s. After that they refreeze and the micropattern disappears in the ice bulk. Transport inside the channel can be obtained by the laser marking process alone. It is caused by the sheer surface tension within the melted area because of the temperature gradient within. The transport observed inside the channels was of the order of 1 mm/s in the laser experimental conditions (1.25 W and 100 mm/s). The temperature increase in the channel depends on the ratio of the laser power over velocity. High temperatures above 50°C can be achieved inside ice cavities. The ii experimental data were compared to theoretical values of the cavities dimensions and temperatures. A valve adapted for a microfluidic in ice functioning upon freezing/melting promoted by laser scanning was tested. The opening of the area depends only on the power and the speed of the laser while the closing time by freezing depends on the cooler devices set temperature. A laser-assisted zone melting technique for the preconcentration of analytes demonstrated on Meldola’s Blue as a model analyte was performed. A travelling melting zone of 1.5 mm x 1.5 mm was scanned at 6% power and 150 mm/sec with 25 scans over an area of 7.5 mm x 1.5 mm. An increase in concentration in end part of the melting zone was monitored after three successive travels. Channels created in conductive frozen solution can be conductive if linked to an electrical power supply. Electrophoresic transport and electroseparation of Rhodamine B and Bromocresol Green in ice capillaries were demonstrated for analytes separation with a power supply (electrical conditions 100 V, 0.1 mA and 3 W). The experimental results were in agreement with theoretical modelling and provide proof for the feasibility of the proposed concept of reconfigurable microfluidic device developed in ice and supported by scanning computer-controlled IR laser.